Science, scientism, and pseudoscience in die Reihe - McBride, N (2016)
This thesis examines the association of science and musical thought that surrounded the Anglophone reception of the West German publication die Reihe (German publication: 1955 – 1962; English edition: 1957 – 1968). While die Reihe presented the early writings of what would become some of the central figures in European compositional circles, the journal’s initial reception was damned through the association of writings of die Reihe with pseudoscience, therefore suggesting that the work was false and to be dismissed. In order to examine the various roles of scientific thought and processes in die Reihe three central areas are explored: to what extent can the epistemological stance of scientism account for the science-like content of the journal? Can a musical journal be considered as a work of pseudoscience? And how did the journal’s portrayal of the composer Anton Webern assist in codifying the musical practices of the authors with the processes and structures of scientific work? It can be seen that scientism can permeate thought and society in multiple and discreet ways, and that scientism can be seen to have influenced policy-makers in post-Second World War West Germany by encouraging a wider application of scientific ideas than had been seen previously. In the same way, the rhetoric of die Reihe’s chief editor, Herbert Eimert, indicates an epistemological stance that is consistent with scientistic values. The initial reception that accused die Reihe of being a work of pseudoscience is critically examined, and it is found that there is insufficient justification for the journal to be considered a work of pseudoscience, because that while it bears a superficial similarity with scientific writing, die Reihe is not itself engaged with scientific work. Finally, it is seen that the way in which Webern’s work and legacy is depicted in the journal is quite unlike how Webern’s work was actually conceived, and as such the framing of Webern as a proto-scientistic composer is another indication of scientism in the thought of die Reihe’s contributors.